2008
DOI: 10.1182/blood-2007-08-109090
|View full text |Cite
|
Sign up to set email alerts
|

The impact of FLT3 internal tandem duplication mutant level, number, size, and interaction with NPM1 mutations in a large cohort of young adult patients with acute myeloid leukemia

Abstract: An internal tandem duplication in the fms-like tyrosine kinase 3 gene (FLT3/ITD) is associated with poor prognosis in acute myeloid leukemia (AML), but the impact of mutant level, size, and interaction with nucleophosmin 1 (NPM1) mutations remains controversial. We evaluated these characteristics in a large cohort of young adult AML patients. There was a highly significant trend for worsening in relapse risk (RR) and overall survival (OS) with increasing FLT3/ITD mutant level (P < .001 for both), and even in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

39
585
10
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 663 publications
(639 citation statements)
references
References 33 publications
39
585
10
5
Order By: Relevance
“…[17][18][19][20][21] More recently, increasing evidence suggests that higher FLT3-ITD to wild-type allelic ratios are associated with poor prognosis. 22 In our patients, FLT3 mutation by itself did not impact DFS. When FLT3-ITD and ABCG2 overexpression occurred together, outcome was significantly worsened with a shorter DFS in double-positive patients.…”
Section: Discussionmentioning
confidence: 46%
“…[17][18][19][20][21] More recently, increasing evidence suggests that higher FLT3-ITD to wild-type allelic ratios are associated with poor prognosis. 22 In our patients, FLT3 mutation by itself did not impact DFS. When FLT3-ITD and ABCG2 overexpression occurred together, outcome was significantly worsened with a shorter DFS in double-positive patients.…”
Section: Discussionmentioning
confidence: 46%
“…These observations point to the interesting possibility that different populations of malignant cells (which are represented by different cell lines) use distinct mechanisms for activating NF-kB. There is a considerable heterogeneity in the response of AML patients to Flt3 inhibitors (Yanada et al, 2005;Knapper, 2007;Gale et al, 2008) or ATMIs (this study), and it will be important to assess the combined proapoptotic effect of kinase inhibitors affecting Flt3 and ATM on preclinical models of AML in the future. Preliminary data obtained with purified CD34 þ BM cells from a limited number of patients suggest that there are two different groups of patients, one group whose marrow blasts respond preferentially to ATMIs and another group that preferentially responds to Flt3 inhibitors.…”
Section: Discussionmentioning
confidence: 88%
“…It is interesting to note that , a recent large study of the Medical Research Council in adult CN-AML also reported a positive effect of NPM1 mutations in the FLT3/ITD-positive group, irrespective of the FLT3/ITD AR. 35 We did not identify differences in the characteristics of FLT3/ITD, that is, AR or ITD length, that could explain why FLT3/ITD did not have a prognostic influence in our NPM1-mutated patients. In addition, SCT could not explain the difference in impact; only a small number of our patients were transplanted, and there were no significant differences in the number of patients transplanted in the various subgroups.…”
Section: Discussionmentioning
confidence: 99%